Pengembangan Pariwisata Kampung Fashion Etnik di Sukoharjo - Muyassaroh, Aqilatul; Purwani, Ofita; Kumoro, Agung (Region : Jurnal Pembangunan Wilayah dan Perencanaan Partisipatif, 2017)
Traditional industries can be utilized for cultural and economic preservation. One of them is ethnic fashion which is currently in favor Â of the fashion designers in Indonesia. Sukoharjo regency is one of the areas in Central Java that has the potential of ethnic fashion which can be the number of craftsmen as well as the number of Â fabric motifs. This ethnic fashion village aims to accommodate ethnic fashion craftsmen in Sukoharjo in order to further develop the tourist industry. In the other hand, architecture is a knowledge that can make the tourism happen. The way is collaborate the component that must have by tourism destination with aspect of architecture like structure, room division, utility, and many more.